2019
DOI: 10.1038/s41586-019-0874-3
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α metabolically controls collagen synthesis and modification in chondrocytes

Abstract: Endochondral ossification, an important bone formation process in vertebrates, highly depends on proper functioning of growth plate chondrocytes 1 . Their proliferation determines longitudinal bone growth and the matrix deposited provides a scaffold for future bone formation. However, these two energy-dependent anabolic processes occur in an avascular environment 1,2 . In addition, the centre of the expanding growth plate becomes hypoxic and local activation of the hypoxiainducible transcription factor HIF-1α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
151
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(173 citation statements)
references
References 51 publications
7
151
0
Order By: Relevance
“…Articular cartilage is residing in a hypoxic microenvironment of avascular hypoxic zone in vivo under normal physiological conditions, ranging from 7∼10% oxygen tensions in the superficial zone, and 1% oxygen in the deep zones (Ferrell and Najafipour, 1992). Hypoxia-inducible factor 1α (HIF-1α) have been demonstrated essential for cartilage maturation (Duval et al, 2009;Stegen et al, 2019). Also, local activation of HIF-1α is necessary for survival and homeostatic function of chondrocytes, as well as normal joint development (Aro et al, 2012;Long, 2019).…”
Section: Regulation Of Hypoxia-inducible Factor-1 In Chondrogenesis Amentioning
confidence: 99%
“…Articular cartilage is residing in a hypoxic microenvironment of avascular hypoxic zone in vivo under normal physiological conditions, ranging from 7∼10% oxygen tensions in the superficial zone, and 1% oxygen in the deep zones (Ferrell and Najafipour, 1992). Hypoxia-inducible factor 1α (HIF-1α) have been demonstrated essential for cartilage maturation (Duval et al, 2009;Stegen et al, 2019). Also, local activation of HIF-1α is necessary for survival and homeostatic function of chondrocytes, as well as normal joint development (Aro et al, 2012;Long, 2019).…”
Section: Regulation Of Hypoxia-inducible Factor-1 In Chondrogenesis Amentioning
confidence: 99%
“…First, in the present study, we have not obtained direct evidence that the abnormal growth plate development in the absence of MAPK7 is caused by an inhibition of HIF1α signaling. Some studies have found that knockout of von Hippel-Lindau tumor suppressor (Vhl) and HIF prolyl hydroxylase 2 (Phd2), two key genes for HIF1α degradation, can increase HIF1α protein levels [46,47]. In our future research, we will investigate whether the observed phenotypes can be rescued by deleting Vhl and/ or Phd2 in chondrocytes.…”
Section: Discussionmentioning
confidence: 95%
“…The critical mediator of cellular adaptation to hypoxia is HIF. Clinical and genetic evidence show that activation of HIF signaling in renal epithelial cells is associated with the development of chronic renal fibrosis and may promote expression and accumulation of ECM 23,42,43 . Recent studies demonstrated that HIF-1α regulates lipid metabolism and the involved key regulator and enzymes [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%